Dampak Relaksasi Otot Progresif dengan Bahasa Daerah terhadap Stres Keluarga dengan Anggota Keluarga yang Mengalami Skizofrenia - Reflin Mahmud; Achir Yani S. Hamid; Herni Susanti; Ice Yulia Wardani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the impact of progressive muscle relaxation using regional languages on family stress who care for family members who experience schizophrenia. The method used in this research is Case Report with a pre-posttest. The results showed that Progressive Muscle Relaxation using Regional Languages could reduce family stress in caring for family members who experience schizophrenia. In conclusion, progressive muscle relaxation interventions with regional languages can help families experiencing stress in caring for family members with schizophrenia. Keywords: Regional Language, Gorontalo, Family, Progressive Muscle Relaxation, Schizophrenia, Stress